The Role of Intersubjectivity in the Production and Appreciation of Humor - Surahmat Surahmat; I Dewa Putu Wijana; Suryo Baskoro (PAROLE: Journal of Linguistics and Education, 2022)
The aim of this study is to investigate the role of intersubjectivity in the production and appreciation of humor. Intersubjectivity is a concept in the phenomenological philosophy that explains the connection of humans to each other. Intersubjectivity  can be used to explain the nature and way of humor works; supplementing the three existing theories of humor namely incongruity theory, superiority theory, and relief theory. This study is a literature review which data were obtained from 30 scientific articles related to humor, intersubjectivity, and the link between the two. Data were excavated using the https://www.connectedpapers.com software. The research stages taken in accordance with the stages of literature review include design, provision of literature (conduct), analysis, and presentation.  The result showed that intersubjectivity has a role because it connects humor makers and connoisseurs through knowledge, feelings, awareness, and even mutual unconsciousness. Funny experiences can arise because makers and connoisseurs can access a “shared world” that allows a certain stimulation to bring out funny feelings that spark laughter. In the production and appreciation of humor intersubjectivity plays a role of (1) providing shared knowledge, (2) asserting the existence of emotions, and (3) directing the meaning of actions.